PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DIGITAL SMART APPS CREATOR PADA MATERI PECAHAN KELAS IV DI SDS YOS SUDARSO MEDAN - Br Ginting, Greace Naomi (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This study examines the validity, practicality, and effectiveness of digital interactive learning media based on Smart Apps Creator for teaching fractions to fourth-grade students at SDS Yos Sudarso Medan. The media was developed using the R&D model with the ADDIE approach, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation by experts and practitioners categorized it as